Implementing the Baghdadi Method to Improve Qur’anic Literacy in Islamic Boarding Schools: Evidence from Roudhotun Nubaha Al Mukhlishin, Mojokerto - Ula Lailatul Khoiriyah; Hilyah Ashoumi; Irwan Ahmad Akbar (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to examine the implementation of the Baghdadi method in improving Qur'anic reading skills among students at Pondok Pesantren Roudhotun Nubaha Al-Mukhlisin Mojokerto, as well as to identify its supporting and inhibiting factors. The background of this research lies in the importance of effective Qur'anic teaching methods to develop basic reading and comprehension skills. This research employed a qualitative descriptive approach. The results show that the implementation of the Baghdadi method is conducted gradually—starting with the introduction of Arabic letters (huruf hijaiyah), mastery of articulation (makharijul huruf), vowel marks (harakat), and eventually progressing to reading and memorizing short surahs. Supporting factors include active involvement from teachers and parents, the use of appropriate instructional media, and high student motivation. Meanwhile, inhibiting factors include limited instructional time, inadequate classroom conditions, and the lack of advanced tajweed instruction.